The Role of Glycemic Control and Vitamin D3 Levels in Modulating mRNA Expression of GLUT4 and IL-6 in Newly Diagnosed Type 2 Diabetes Mellitus Patients: Diabetes Mellitus - Fatkhurrohman, Imam; Aman, Andi Makbul; Umar, Husaini; Bukhari, Agussalim; HS, Heri Nugroho; Sanusi, Himawan; Hatta, Mochammad; Zainuddin, Andi Alfian (Journal of Neonatal Surgery, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and chronic low-grade inflammation. The molecular mechanisms of glucose transport and inflammation in T2DM are influenced by both glycemic status and vitamin D3 levels, particularly through their effects on GLUT4 and interleukin-6 (IL-6) expression. Methods: This cross-sectional study involved 34 newly diagnosed male T2DM patients aged 40–60 years. Glycated hemoglobin (HbA1c), serum 25(OH)D3, and IL-6 levels were measured using ELISA, and mRNA expression of GLUT4 was assessed by RT-qPCR. Correlation analysis and path analysis (PLS-SEM) were performed to evaluate the direct and indirect relationships among variables. Results: HbA1c levels showed a significant negative correlation with GLUT4 expression (r = –0.711, p < 0.001) and a positive correlation with IL-6 levels (r = 0.747, p < 0.001). Vitamin D3 levels mediated the effect of glycemic control on both IL-6 and GLUT4, with significant indirect effects observed (p < 0.05). Path analysis revealed that vitamin D3 partially mediated the relationship between HbA1c and molecular markers of inflammation and glucose transport. Conclusion: Poor glycemic control is associated with increased IL-6 and decreased GLUT4 expression in newly diagnosed T2DM patients. Vitamin D3 plays a mediating role in this mechanism and may serve as a therapeutic adjunct to modulate inflammation and glucose transport at the molecular level. These findings highlight the metabolic significance of vitamin D beyond bone health, particularly in the early management of T2DM.